2018
DOI: 10.22159/ajpcr.2018.v11i2.23160
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Hazards in Pharmaceutical Industry: An Overview

Abstract: The pharmaceutical industry is a vital component of health-care systems all over the world engaged in discovery, development, manufacture, and marketing of medicines for human as well as animal health. Pharmaceutical industries also have many environmental problems, like the other chemical industries. The pharmaceutical industry is based primarily on the scientific formulation, research, and development of drugs, that is, helpful in the prevention or treatment of diseases and disorders. The manufacturing of AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…8 Despite the clinical relevance of the excipients, recent studies have shown that some of these excipients are not environmentally friendly. 10,11…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Despite the clinical relevance of the excipients, recent studies have shown that some of these excipients are not environmentally friendly. 10,11…”
Section: Introductionmentioning
confidence: 99%
“…8 Despite the clinical relevance of the excipients, recent studies have shown that some of these excipients are not environmentally friendly. 10,11 Several research groups have shown the impact of the toxic solvent systems used in pharmaceutical industries. 10,11 In particular, in protein stability studies, it has been reported that solvents not only interact with the structure of proteins but also play a dominant role in their toxicity profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity and combinations of these substances is so great that it is impossible to list them all. Quite a big problem are fillers, i.e., inert agents aimed at improving the appearance, durability or supporting the solubility of the finished product [ 14 ]. Fillers pose a serious risk of poisoning workers, and the properties of these agents can lead to ignition or explosion.…”
Section: Chemical Risk In the Pharmaceutical Industrymentioning
confidence: 99%
“…The frequency and effects of chemical hazards have increased significantly in recent years, which is also due to the development of the chemical industry. By industrial hazard, we mean a condition that causes human injury, disease or death [ 14 ]. There are hazards in the production of drugs with the following substances and mixtures: With explosive properties; With oxidizing properties; Extremely flammable; Highly flammable; Very toxic; Harmful; Corrosive, irritating item; Sensitizing; Mutagenic; Toxic for reproduction; Dangerous for the environment [ 15 ].…”
Section: Chemical Risk In the Pharmaceutical Industrymentioning
confidence: 99%